Screening of grapevine red blotch virus in two European ampelographic collections - Jean-Sébastien Reynard; Justine Brodard; Nathalie Dubuis; Isabelle Kellenberger; Anne-Sophie Spilmont; David Roquis; Varvara Maliogka; Cécile Marchal; Sandrine Dedet; Ophélie Gning; Daniel Croll; Katia Gindro; et al. (Journal of Plant Pathology, 2022)
Grapevine red blotch virus (GRBV) is a recently identified virus that infects grapevine and has a severe impact on the grape industry in North America. Since the first description of the virus 8 years ago, clear progress has been made regarding our understanding of the GRBV pathosystem. However, questions remain regarding the origin of this pathogen and its spread outside North America, especially in Europe. In this study, we present the results of a large-scale GRBV survey in two European repositories; we targeted Vitis spp. accessions with diverse geographical origins. Of 816 accessions from different origins (50 different countries around the world), six accessions were infected by GRBV, all of which originated from the United States. We investigated the DNA virome of 155 grapevine accessions from the Swiss grapevine collection using high-throughput sequencing. We observed that virome of the Swiss grapevine collection was composed of several RNA viruses. In contrast, we did not detect any DNA viruses in the 155 Swiss grapevine accessions. This finding suggests that the abundance of DNA viruses infecting grapevines in Switzerland is either very low or non-existent. Our results and the findings of studies published since 2008 show that GRBV most likely originated in North America and subsequently spread to other viticultural areas in the world via unintentional movement of infected cuttings. According to our data, the most plausible scenario for the origin of GRBV is that the virus evolved from non- Vitis vinifera hosts and underwent a host jump to Vitis vinifera after its introduction to North America in the 1600s.

Tree-rings and people – different views on the 1540 Megadrought. Reply to Büntgen et al. 2015 - Christian Pfister; Oliver Wetter; Rudolf Brázdil; Petr Dobrovolný; Rüdiger Glaser; Jürg Luterbacher; Sonia I. Seneviratne; Eduardo Zorita; Maria-Joao Alcoforado; Mariano Barriendos; Ursula Bieber; Karl H. Burmeister; et al. (Climatic Change, 2015)

Erratum to: The year-long unprecedented European heat and drought of 1540 – a worst case - Oliver Wetter; Christian Pfister; Johannes P. Werner; Eduardo Zorita; Sebastian Wagner; Sonia I. Seneviratne; Jürgen Herget; Uwe Grünewald; Jürg Luterbacher; Maria-Joao Alcoforado; Mariano Barriendos; Ursula Bieber; et al. (Climatic Change, 2014)

The year-long unprecedented European heat and drought of 1540 – a worst case - Oliver Wetter; Christian Pfister; Johannes P. Werner; Eduardo Zorita; Sebastian Wagner; Sonia I. Seneviratne; Jürgen Herget; Uwe Grünewald; Jürg Luterbacher; Maria-Joao Alcoforado; Mariano Barriendos; Ursula Bieber; et al. (Climatic Change, 2014)